Alteration in the expression of MGMT and RUNX3 due to non-CpG promoter methylation and their correlation with different risk factors in esophageal cancer patients. Issue 5 (April 2017) - Saikia, Snigdha; Rehman, Asad Ur; Barooah, Prajjalendra; Sarmah, Preeti; Bhattacharyya, Mallika; Deka, Muktanjalee; Deka, Manab; Goswami, Bhabadev; Husain, Syed Akhtar; Medhi, Subhash
Promoter methylation reflects in the inactivation of different genes like O 6 -methylguanine-DNA methyltransferase DNA repair gene and runt-related transcription factor 3, a known tumor suppressor gene in various cancers such as esophageal cancer. The promoter methylation was evaluated for O 6 -methylguanine-DNA methyltransferase and runt-related transcription factor 3 in CpG, CHH, and CHG context (where H is A, T, or C) by next-generation sequencing. The methylation status was correlated with quantitative messenger RNA expression. In addition, messenger RNA expression was correlated with different risk factors like tobacco, alcohol, betel nut consumption, and smoking habit. CpG methylation of O 6 -methylguanine-DNA methyltransferase promoter had a positive association in the development of esophageal cancer (p < 0.05), whereas runt-related transcription factor 3 promoter methylation showed no significant association (p = 1.0) to develop esophageal cancer. However, the non-CpG methylation, CHH, and CHG were significantly correlated with O 6 -methylguanine-DNA methyltransferase (p < 0.05) and runt-related transcription factor 3 (p < 0.05) promoters in the development of esophageal cancer. The number of cytosine converted to thymine (C→T) in O 6 -methylguanine-DNA methyltransferase promoter showed a significant correlation between cases and controls (p < 0.05), but in runt-related transcription factor 3 no such significant correlation was observed. Besides, messenger RNA expression was found to be significantly correlated with promoter hypermethylation of O 6 -methylguanine-DNA methyltransferase and runt-related transcription factor 3 in the context of CHG and CHH (p < 0.05). The CpG hypermethylation in O 6 -methylguanine-DNA methyltransferase showed positive (p < 0.05) association, whereas in runt-related transcription factor 3, it showed contrasting negative association (p = 0.23) with their messenger RNA expression. Tobacco, betel nut consumption, and smoking habits were associated with altered messenger RNA expression of O 6 -methylguanine-DNA methyltransferase (p < 0.05) and betel nut consumption and smoking habits were associated with runt-related transcription factor 3 (p < 0.05). There was no significant association between messenger RNA expression of O 6 -methylguanine-DNA methyltransferase and runt-related transcription factor 3 with alcohol consumption (p = 0.32 and p = 0.15). In conclusion, our results suggest that an aberrant messenger RNA expression may be the outcome of CpG, CHG, and CHH methylation in O 6 -methylguanine-DNA methyltransferase, whereas outcome of CHG and CHH methylation in runt-related transcription factor 3 promoters along with risk factors such as consumption of tobacco, betel nut, and smoking habits in esophageal cancer from Northeast India.